Avaliação do herbicida saflufenacil no controle de Ipomoea grandifolia (Dammer) O’Donell e Euphorbia heterophylla L. no sistema de cana crua - Costa, Saulo Italo de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The effectiveness of herbicides in raw cane agricultural system is directly impacted by the amount and distribution of straw in the field, which intercept the herbicide before it reaches the ground as well as the occurrence of rain after application. Thus, this study aimed to evaluate the effectiveness of the herbicide saflufenacil alone and mixed with adjuvant to control of Euphorbia heterophylla and Ipomoea grandifolia weeds in sugarcane mechanical harvesting without straw burning, as well as its selectivity to the culture. The study was carried out in three phases: one in greenhouse and two at the field (Lençóis Paulista - SP and Teotônio Vilela - AL) with different doses of saflufenacil herbicide, with or without rain simulation, at different times after application of chemical treatments. The treatments were: saflufenacil (0.050 kg ha- 1); saflufenacil (0.070 kg ha-1); saflufenacil (0.140 kg ha- 1); saflufenacil + Dash (0.050 kg ha-1 + 0.5 % v / v); saflufenacil + Dash ( 0.070 kg ha-1 + 0.5% v / v); saflufenacil + Dash ( 0.140 kg ha-1 + 0.5% v / v) and mesotriona + Assist ( 0.3 L.ha-1 + 0.5% v / v ), which were applied on 12 t ha-1 of straw on the ground, as well as spraying on the soil without straw coverage, in the presence or absence of simulated rain (amount of 11 mm) after spraying of the chemical treatments. To the 3, 7, 14, 21 and 28 days after application (DAA), the percentage of control was evaluated and at 28 DAA the dry biomass of the weed species was evaluated. The saflufenacil herbicide applied in post-emergence was effective to control of I. grandifolia and E. heterophylla weeds. The weed I. grandifolia proved to be more sensitive to treatment with the saflufenacil herbicide. The presence of straw and the absence of rain facilitated the control of I. grandifolia, while the presence of straw and rain did not facilitated the control of E. heterophylla. The adjuvant addition to ...

eficácia dos herbicidas no sistema de cana-crua é diretamente influenciada pela quantidade e distribuição de palhiço na área por interceptar o herbicida antes que este atinja o solo, bem como pela ocorrência de chuvas após a aplicação. Com isso, esse estudo objetivou avaliar a eficácia do herbicida saflufenacil isolado e em mistura com adjuvante no controle das plantas daninhas Ipomoea grandifolia e Euphorbia heterophylla aplicado em pós-emergência no sistema de cana-crua, bem como a seletividade do herbicida a cultura da cana-de-açúcar. O estudo foi realizado em três fases uma em casa de vegetação e duas a campo (Lençóis Paulista-SP e em Teotônio Vilela-AL), com diferentes doses de saflufenacil, com ou sem simulação de chuva, em tempos distintos após a aplicação dos tratamentos químicos. Os tratamentos utilizados foram: saflufenacil (0,050 kg ha-1), saflufenacil (0,070 kg ha-1), saflufenacil (0,140 kg ha-1), saflufenacil + Dash (0,050 kg ha-1 + 0,5% v/v); saflufenacil + Dash (0,070 kg ha-1 + 0,5% v/v); saflufenacil + Dash (0,140 kg ha-1 + 0,5% v/v); e mesotriona + Assist (0,3 L ha-1 + 0,5% v/v), os quais foram aplicados sobre 12 t de palhiço ha-1 sobre o solo, além da pulverização sobre o solo sem cobertura de palhiço, na presença ou ausência de simulação de chuva, na quantidade de 11 mm, após a pulverização dos tratamentos químicos. Aos 3, 7, 14, 21 e 28 dias após a aplicação (DAA) foi avaliada a porcentagem de controle e aos 28 DAA fez-se a avaliação de biomassa seca das espécies de plantas daninhas em estudo, no sistema de colheita de cana crua. O herbicida saflufenacil, aplicado em pós-emergência, na cultura da cana-de-açúcar foi eficaz no controle de I. grandifolia e E. heterophylla. A espécie I. grandifolia foi mais sensível aotratamento com o herbicida saflufenacil. A presença de palhiço e a ausência de chuva favoreceram o controle ...
Keywords: Cana-de-açúcar - Doenças e pragas; Erva daninha - Controle; Herbicidas; Euforbia; Sugar-cane